Engagement with indigenous people preserves local knowledge and biodiversity alike - Aida Shafreena, Ahmad Puad; Gardner, Elliot M; Pereira, Joan T.; Jugah, Tagi; Salang, Nyegang; Postar, Miun; Jumian, Jeisin; Pokorny, Lisa; Zerega, Nyree J.C. (Elsevier Science, Ltd., 2022)
Indigenous peoples are important stewards of biodiversity, often living near and possessing intimate knowledge of ecosystems. As a result, species new to science may be long known to indigenous people. While the scientific endeavor has long benefitted from indigenous knowledge, it has usually not engaged with it on equal footing1,2. While Linnaean taxonomy offers a broad framework for global comparisons, it may lack the detailed local insights possessed by indigenous peoples. This study illustrates how meaningful engagement with indigenous knowledge — throughout the scientific process — can improve biodiversity science and promote conservation1,2, particularly in studies of crop wild relatives, an international priority3 for food security in the face of climate change4. Two species of fruit trees recognized as distinct by the Iban and Dusun peoples, but considered a single species in current Linnaean taxonomy, were confirmed as distinct taxa by molecular studies. They correspond to Artocarpus odoratissimus Blanco and Artocarpus mutabilis Becc., whose distinguishing characteristics were clarified by members of indigenous communities.